(untitled) (Plant Bulletin, 2025)
Soil erosion represents one of the most significant global threats to environmental integrity, agricultural productivity, and food security. Current estimates suggest that over 75 billion tonnes of soil are lost annually, with approximately one-third of the world’s arable land classified as moderately to severely degraded. Besides decreasing the soil fertility, this process changes the hydrological cycles, enhancing the emission of greenhouse gases, and impacting national economies that rely on agriculture adversely. The current study is a synthesis of peer-reviewed materials, world soil data, and quantitative evaluations aimed at assessing the theory, cause, and effects of soil erosion as well as evaluation of the developing mitigation measures. Review uses an integrative structure integrating comparative case study, GIS-based modeling, and policy review to determine current gaps in the research field and evaluate the success of current interventions to protect the soil. The results indicate that current erosion control measures are scattered and regionally specific whereby there is inadequate integration of remote sensing, microbial stabilization of soils, and socio-economic assessment processes. To bring any meaningful improvements, new research and management approaches should be holistic and data-intensive, combining powerful models with participatory land-management and policy models. The general objective of this review is to improve the knowledge about the multifaceted mechanisms of soil erosion processes, to advance new, interdisciplinary approaches that will build soil erosion resilience and protect agricultural performance and environmentally sustainable stewardship, both locally and globally.